Efektivitas Pelaksanaan Program Sembako di Desa Tapadaka Satu Kecamatan Dumoga Tenggara Kabupaten Bolaang Mongondow Provinsi Sulawesi Utara - Telsa Paputungan; Irawaty Igirisa; Rahmatia Pakaya (Perspektif Administrasi Publik dan hukum, 2026)
This research aims to analyze the effectiveness of the implementation of the staple food assistance program in Tapadaka Satu Village, Dumoga Tenggara Sub-district, Bolaang Mongondow Regency, Sulawesi Utara Province. The main sub-focus of this research includes five aspects of effectiveness measurement proposed by Sutrisno (2018), namely: (1) program understanding, (2) target accuracy, (3) timeliness, (4) achievement of objectives, and (5) real change. This research employs a qualitative, descriptive research approach. Data collection techniques include interviews, observation, and documentation. The results indicate that the implementation of the staple food assistance program in Tapadaka Satu Village has not been fully effective. In terms of program understanding, socialization has been conducted by the Social Affairs Office and village government, but some beneficiary families still do not fully understand the program’s mechanisms, rights, and obligations. In target accuracy, discrepancies in beneficiary data persist due to changing socio-economic conditions and the suboptimal updating of DTSEN data. In timeliness, assistance distribution generally follows the mechanism, but delays in fund disbursement still occur. In achieving objectives, the program helps reduce beneficiary families’ food expenditure burden, although delays affect results. Lastly, real change remains limited, short-term, and has not significantly improved community welfare.